PERAN DIRECTOR OF PHOTOGRAPHY DALAM PEMBUATAN FILM DOKUMENTER BERJUDUL "SUARA KELUARGA" - Hafizh Irsyad Ananto, (2023)
The documentary film titled "Suara Keluarga" discusses the influence of family communication patterns on teenagers' social interactions. This documentary aims to provide understanding and awareness to the public about the importance of healthy family communication patterns in shaping the character and social relationships of teenagers. Ultimately, the film shows that there is a connection between the communication patterns used in the family and the formation of character and social interactions among teenagers. The conclusion of this film is that the family, as the primary source of communication, has a far more significant influence than the environment in shaping a child's personality and character formation. It is important to consider what type of family communication pattern is best to use in raising a child. The role of the Director of Photography in the making of this film is crucial in determining the shots and angles to achieve the best visual results.